Theoretische Grundlagen und elektronisches Wörterbuch der lexikalischen Parallelen des Ukrainischen und Deutschen - Dubichynskyi, Volodymyr; Gamzayev, Rustam; Reuther, Tilmann (Wiener Slawistischer Almanach, 2023)
The article presents elements of the theory and technique of the lexicographic description of lexical parallels used in the printed and electronic dictionaries of lexical parallels of Ukrainian and German. On the one hand, the concepts of lexical parallel, intersememe, idiosememe, interonym, interlingual homonymy and interlingual paronymy, as well as dictionary article, vocabulary and keyword are introduced and partly redefined. On the other hand, the information technology procedure of transferring the lexicographic material into a database is explained and the resulting user interface is demonstrated.